X-ray irradiation synthesis of PEG-coated Au-Pd nanoparticles. (6th August 2015) - Li, Min-Tsang; Wang, Chang-Hai; Lai, Sheng-Feng; Ong, Edwin B L; Chen, Y H; Lin, Chung-Kwei; Margaritondo, G; Hwu, Y
Abstract: We demonstrate that the combination of x-ray irradiation and capping by polyethylene glycol (PEG) produces excellent flexibility in controlling the structure of Au–Pd nanoparticles while preserving their catalytic performance. We specifically adopted two different fabrication methods: co-reduction and seed-assisted reduction. In both cases, precursor composition plays an important role in controlling the phases and size of the bimetallic nanoparticles. The optimal catalytic performance is obtained with the highest Pd concentration and when the nanoparticles consist of a Au core and a Pd shell.